2016
DOI: 10.1016/j.cellimm.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic nanoparticles to induce immunologic tolerance: Prevention and reversal of FVIII inhibitor formation

Abstract: a b s t r a c tThe immune response of hemophilia A patients to administered FVIII is a major complication that obviates this very therapy. We have recently described the use of synthetic, biodegradable nanoparticles carrying rapamycin and FVIII peptide antigens, to induce antigen-specific tolerance. Herein we test the tolerogenicity of nanoparticles that contains full length FVIII protein in hemophilia A mice, focusing on anti-FVIII humoral immune response. As expected, recipients of tolerogenic nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…They demonstrated that NP containing both the immunosuppressant rapamycin and an antigen (coagulation factor VIII) inhibited antigen-specific CD4 + and CD8 + T-cell activation, increased regulatory cells, induced durable B-cell tolerance, and inhibited antibody responses against coagulation factor VIII. Subsequently, two studies reported that co-administration of free antigen and SVP containing rapamycin (SVP-Rapa) induced antigen-specific and SVP-Rapa-dependent immune tolerance in mice and non-human primates [18], [19]. In this study, we demonstrate that SVP-Rapa can induce immune tolerance to rhGAA and improve efficacy of ERT in GAA-knockout (KO) mice that is superior to immunosuppression with MTX.…”
Section: Introductionmentioning
confidence: 62%
“…They demonstrated that NP containing both the immunosuppressant rapamycin and an antigen (coagulation factor VIII) inhibited antigen-specific CD4 + and CD8 + T-cell activation, increased regulatory cells, induced durable B-cell tolerance, and inhibited antibody responses against coagulation factor VIII. Subsequently, two studies reported that co-administration of free antigen and SVP containing rapamycin (SVP-Rapa) induced antigen-specific and SVP-Rapa-dependent immune tolerance in mice and non-human primates [18], [19]. In this study, we demonstrate that SVP-Rapa can induce immune tolerance to rhGAA and improve efficacy of ERT in GAA-knockout (KO) mice that is superior to immunosuppression with MTX.…”
Section: Introductionmentioning
confidence: 62%
“…In order to limit global immune suppressive effects of rapamycin, nanoparticle technologies have been developed to package rapamycin. When co-packaged or co-administered with antigen, tolerance may be induced [59, 60]. Approaches to antigen-specific tolerance induction without the use of immune suppressive drugs include oral tolerance induction, as shown by a recent proof-of-concept study [61].…”
Section: Preventing Immune Responses – From Global Immune Suppressmentioning
confidence: 99%
“…From the above examples, it can be concluded that the first generation of nanovaccines can enhance efficient antigen (Ag) delivery to lymphoid organs (e.g., peripheral lymph nodes), promote cytosolic delivery and cross presentation in the dendritic cells (DCs), and activate T cells, However, without any co-stimulatory molecule expression or cytokine secretion, the vaccine effect is still limited and there is a high likelihood of inducing immune tolerance [51]; additional immune stimulators may be incorporated in nanovaccines to reduce this risk.…”
Section: Antigen Delivery and Presentationmentioning
confidence: 99%